1994
DOI: 10.1161/01.str.25.12.2463
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide promotes arteriolar dilation during cortical spreading depression in rabbits.

Abstract: Background and Purpose Pial arterioles transiently dilate during cortical spreading depression (CSD), although the mechanisms are unclear. We tested the hypothesis that increased production of nitric oxide (NO) promotes arteriolar dilation.Methods Urethane-anesthetized rabbits were equipped with cranial windows, and the diameter (reported in micrometers) of a pial arteriole was determined via intravital microscopy. In each rabbit, a baseline CSD was elicited by microapplication of KC1 onto the cortex, and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
(57 reference statements)
3
18
0
Order By: Relevance
“…NMDA can cause CSD when directly applied to the hippocampus (C. Ayata, unpublished observations), cerebral cortex, or cerebellum (29,38). CSD was a major contributor to NMDA-induced vasomotor responses in our experiments, because 1) NMDA-induced vascular changes were abrupt, and the peak dilation was transient; 2) there was often a superimposed early and brief decrease in vessel caliber, reminiscent of the hypoperfusion observed in mouse and rat cortex during KCl-induced CSDs (3,14); 3) this vasoconstriction was augmented after L-NNA superfusion as previously reported for CSD-induced CBF changes in mice and other species (3,8,9,13,14); and 4) on washout of NMDA, a delayed and prolonged vasoconstriction was observed, possibly reflecting post-CSD oligemia.…”
Section: Discussionsupporting
confidence: 64%
“…NMDA can cause CSD when directly applied to the hippocampus (C. Ayata, unpublished observations), cerebral cortex, or cerebellum (29,38). CSD was a major contributor to NMDA-induced vasomotor responses in our experiments, because 1) NMDA-induced vascular changes were abrupt, and the peak dilation was transient; 2) there was often a superimposed early and brief decrease in vessel caliber, reminiscent of the hypoperfusion observed in mouse and rat cortex during KCl-induced CSDs (3,14); 3) this vasoconstriction was augmented after L-NNA superfusion as previously reported for CSD-induced CBF changes in mice and other species (3,8,9,13,14); and 4) on washout of NMDA, a delayed and prolonged vasoconstriction was observed, possibly reflecting post-CSD oligemia.…”
Section: Discussionsupporting
confidence: 64%
“…As expected, L-NAME increased systemic blood pressure, reduced resting NO levels, and significantly diminished the biphasic NO response to SD (385). Although L-NAME has antimuscarinic effects that may be confounding, N-nitro-L-arginine (L-NA), which is a more specific NOS inhibitor, also reversibly suppressed SD-induced peak hyperemia by up to 40 -70% when applied topically or systemically in rabbits (65,66,314,315). Moreover, 7-nitroindazole (7-NI), a relatively specific inhibitor of neuronal NOS in vivo, also reduced the peak hyperemia to SD by 35%, without a significant change in resting CBF or systemic blood pressure, implicating a neuronal origin for NO (66).…”
Section: Nosupporting
confidence: 52%
“…For example, increased shear stress has been shown to selectively activate mitochondria in endothelium and secondarily promote relaxation of smooth muscle of human coronary arteries (29,30). In addition, cortical spreading depression depolarizes mitochondria in neurons but not in astroglia and we have shown that NO is an important mediator of vasodilation (7,8,16). Thus we propose that cell specific mitochondrial depolarization in the neurovascular unit during changes in physiological status, such as occurs during neuronal activation, will lead to appropriate blood flow changes due to production of NO.…”
Section: Discussionmentioning
confidence: 70%
“…We also examined the effects of BMS on relaxation of endothelium-denuded cerebral arteries, which contain intact perivascular innervation, to demonstrate that our studies in cultured neurons are supported by results from naturally occurring neurons. nNOS is located in perivascular nerves supplying the cerebral vasculature (39), and NO from both the perivascular (7,8,39) and parenchymal neurons (31) has access via diffusion to the cerebral vasculature. Although several investigators have indicated that nNOS or other NOS isoforms are present in mitochondria as well as in the cytosol, the prevailing evidence does not support a mitochondrial localization of NOS under basal conditions in neurons or cardiac cells (25,44).…”
Section: The Current Study Provides Evidence That Pharmacological Depmentioning
confidence: 99%